Bilingualism Effect in Learning English Process (Study at SMA 3 Tana-Toraja) - Fither; Ammade, Salasiah; Amaluddin (Universitas Islam Ahmad Dahlan (UIAD), 2023)
In learning English in Toraja regional schools, bilingualism occurs in the process because full English in the learning process will make it difficult for students in terms of learning flow. The use of bilingualism in the classroom affects the learning process and this makes researchers interested in getting deeper data about its effect on the learning process. Based on these problems, this study aims to determine the effect of bilingualism in the learning process at SMA Negeri 3 Tana-Toraja and students' perceptions of it. This study used qualitative design using observation notes and interview as the research instruments. The research setting was at SMA Negeri 3 Tana Toraja with a population consisting of 2 classes in eleventh grade. In data collection, samples were selected using purposive random sampling, and class X1 A was taken as the selected sample with 30 students and 1 teacher as the interviewee. The results showed that students were very enthusiastic about the lessons presented based on observation notes. Furthermore, students understood more quickly and their vocabulary increased a lot with the bilingualism method, students feel comfortable in learning, eliminate their doubts when asked, and understand the lesson more quickly. It can be concluded that bilingualism in learning English makes it easier for students to understand lessons more quickly or to memorize new words in English.